SEKSUALITAS, TUBUH DAN KENDALI PEREMPUAN - Finisia Angelina Tantular; Endah Triwijati; Teguh Wijaya Mulya (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to understand how Anjani formed into a woman who has a differe nt perspective to women in general and able to make decisions related to the body and sexuality are very different from the dominant discourse. This descriptive qu alitative research method Intrinsic Case Studies with Postrukturalis Feminist Perspective. The process of data collection is done by using in-depth interviews. The analysis is thematic analysis. The results of this study indicate that the experience Anjani with her father formed her mind so to live a relationship with men tend to be in control and experience formed through discourses obtained through the books with the theme of women who are often her read and the experiences of her friends helped shape her thinking so that her will be woman who are resistant patriarchal culture that had been shackled women.